Measuring Job Performance of The Economic Creative Business upon Women Enterpreneurs Base (Case Study at Online Bunda Community Bogor Branch Using Balance Scorecard Approach) - Indar Khaerunnisa (STIE Binaniaga, 2018)
Balance scorecard has a privilege in terms of coverage measurement whichis a fairly comprehensive because while taking into consideration the financialperformance. Balance scorecard also consider the performance of non-financialperformance, namely customer, internal business processes, and learning and growth.Referring to the problems encountered by Member of Bunda Online Community, thisresearch examines: